Penerapan Strategi Experiential Marketing Brand Nescafé dalam Promosi Nescafé Ice Roast - Simanjuntak, Daniel; Anita Fauzah; Rizki Muhammad Ardian Setiadi; Maysitha Fitri Az Zahra (Jurnal Ilmiah Neraca : Ekonomi Bisnis, Manajemen, Akuntansi, 2025)
This study aims to analyze the experiential marketing strategy implemented by the Nescafé brand in promoting its Nescafé Ice Roast product. The research employs a qualitative method with a descriptive approach, based on Schmitt’s (1999) Experiential Marketing framework, which consists of five core dimensions: sense, feel, think, act, and relate. Data were collected through literature review, observation of promotional content, and analysis of Nescafé’s marketing activities for the Ice Roast campaign. The findings reveal that Nescafé applies the sense dimension through attractive packaging and visual advertising; the feel dimension by creating refreshing and enjoyable emotional experiences; the think dimension with creative messages that align with the lifestyle of young consumers; the act dimension by encouraging consumer interaction through digital activations and events; and the relate dimension by fostering a sense of togetherness and identity within the urban youth community.